Human adipocyte differentiation and composition of disease-relevant lipids are regulated by miR-221-3p - Ahonen, Maria A.; Asghar, Muhammad Yasir; Parviainen, Suvi J.; Liebisch, Gerhard; Höring, Marcus; Leidenius, Marjut; Fischer-Posovszky, Pamela; Wabitsch, Martin; Mikkola, Tomi S.; Törnquist, Kid; Savolainen-Peltonen, Hanna; Haridas, P.A. Nidhina; et al. (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
MicroRNA-221-3p (miR-221-3p) is associated with both metabolic diseases and cancers. However, its role in terminal adipocyte differentiation and lipid metabolism are uncharacterized. miR-221-3p or its inhibitor was transfected into differentiating or mature human adipocytes. Triglyceride (TG) content and adipogenic gene expression were monitored, global lipidome analysis was carried out, and mechanisms underlying the effects of miR-221-3p were investigated. Finally, cross-talk between miR-221-3p expressing adipocytes and MCF-7 breast carcinoma (BC) cells was studied, and miR-221-3p expression in tumor-proximal adipose biopsies from BC patients analyzed. miR-221-3p overexpression inhibited terminal differentiation of adipocytes, as judged from reduced TG storage and gene expression of the adipogenic markers SCD1, GLUT4, FAS, DGAT1/2, AP2, ATGL and AdipoQ, whereas the miR-221-3p inhibitor increased TG storage. Knockdown of the predicted miR-221-3p target, 14-3-3γ, had similar antiadipogenic effects as miR-221-3p overexpression, indicating it as a potential mediator of mir-221-3p function. Importantly, miR-221-3p overexpression inhibited de novo lipogenesis but increased the concentrations of ceramides and sphingomyelins, while reducing diacylglycerols, concomitant with suppression of sphingomyelin phosphodiesterase, ATP citrate lyase, and acid ceramidase. miR-221-3p expression was elevated in tumor proximal adipose tissue from patients with invasive BC. Conditioned medium of miR-221-3p overexpressing adipocytes stimulated the invasion and proliferation of BC cells, while medium of the BC cells enhanced miR-221-3p expression in adipocytes. Elevated miR-221-3p impairs adipocyte lipid storage and differentiation, and modifies their ceramide, sphingomyelin, and diacylglycerol content. These alterations are relevant for metabolic diseases but may also affect cancer progression. •miR-221-3p suppresses adipogenesis, putatively mediated by 14-3-3γ downregulation.•miR-221-3p suppresses de novo lipogenesis in adipocytes.•miR-221-3p alters adipocyte ceramide, sphingomyelin and diacylglycerol content.•miR-221-3p expression is elevated in adipocytes adjacent to breast carcinoma.•Adipocyte miR-221-3p elevation may promote metabolic disease and cancer progression.